DETERMINATION OF SPECIAL PERMIT RATE FOR LARGESCALE SOLAR DEVELOPMENT IN JOHOR BASED ON PLANNER PERSPECTIVE - Sahid, Mohd Shahrizan; Suratman, Robiah; Mohd Ali, Hishamuddin (PLANNING MALAYSIA, 2021)
Over the past decade, the Malaysian government has put its effort into various programmes to promote solar energy in the country. As for now, Large Scale Solar (LSS) is the biggest programme conducted by Sustainable Energy Development Authority (SEDA) and permitted by Energy Commission (EC). As the large-scale solar does not have any proper guideline, especially in development approval consideration, Johor land administrators have put telecommunication tower development as a benchmark in approving large-scale solar developments that use the Special Permit method. However, the Special Permit fee appears unfitting for the development. Thus, this paper aims to determine the Special Permit rate for large-scale solar development which are profitable to the stakeholders. Its drawback is particularly related to solar radiance, which is the key criterion of site selection to develop the most profitable site. Selected respondents have been interviewed and the findings have led to a direction to standardise a legal framework for large-scale solar, especially in Johor.